1996
DOI: 10.1111/j.1349-7006.1996.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in vitro Tumor Cell Invasion by Ginsenoside Rg3

Abstract: The effect of plant glycosides on tumor cell invasion was examined. Among the glycosides tested, ginsenoside Rgs was found to be a potent inhibitor of invasion by rat ascites hepatoma cells (MM1), B16FE7 melanoma cells, human small cell lung carcinoma (OC10), and human pancreatic adenocarcinoma (PSN‐1) cells, when examined in a cell monolayer invasion model. Structurally analogous ginsenosides, Rb2, 20(R)‐ginsenoside Rg2 and 20(S)‐ginsenoside Rg3 (a stereoisomer of Rg3), showed little inhibitory activity. Neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 26 publications
1
77
0
1
Order By: Relevance
“…This in turn results in the activation of downstream caspase-3, which cleaves ParP (24,25). recent data indicate that the mitochondrial pathway is controlled and regulated by Bcl-2 family protein (5,(22)(23)(24)(25). Bcl-2 family proteins such as Bcl-2 and Bax have been identified as major regulators in controlling the release of mitochondrial cytochrome c (26).…”
Section: (S)-rg3 Induced Apoptosis By Activating Ampkmentioning
confidence: 99%
“…This in turn results in the activation of downstream caspase-3, which cleaves ParP (24,25). recent data indicate that the mitochondrial pathway is controlled and regulated by Bcl-2 family protein (5,(22)(23)(24)(25). Bcl-2 family proteins such as Bcl-2 and Bax have been identified as major regulators in controlling the release of mitochondrial cytochrome c (26).…”
Section: (S)-rg3 Induced Apoptosis By Activating Ampkmentioning
confidence: 99%
“…Imamura et al [21] found that the addition of serum to a suspension of highly invasive tumor cells induced an increase in the intracellular pH, as well as a transient elevation of intracellular calcium, whereas the addition of serum to a poorly invasive clone did not result in changes in intracellular pH or calcium. Moreover, we [22] found that the addition of 1-oleoyllysophosphatidic acid to rat ascites hepatoma cells resulted in an instantaneous increase in intracellular calcium, but when these cells were pretreated with the antimetastatic agent, ginsenoside Rg3, the intracellular calcium spike induced by 1-oleoyl-lysophosphatidic acid was completely abolished. Hellmich et al [23] found that bombesin induced either intracellular calcium oscillations or biphasic elevation in intracellular calcium, and that the activation of mitogen-activated protein kinase (MAPK) kinase (MEK) was important for maintaining the elevated intracellular calcium levels induced by bombesin.…”
Section: Discussionmentioning
confidence: 90%
“…Ginsenoside Rg3, the active ingredient extracted from Panax ginseng, possesses anticancer properties and exerts various pharmacological effects (6,7). Previous studies demonstrated that ginsenoside Rg3 may inhibit cancer growth in vitro and in vivo and is considered to be relatively safe (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%